2018
DOI: 10.1111/1911-3846.12352
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of SEC Enforcement and Auditor Reporting Decisions

Abstract: We find that non‐Big 4 audit offices with greater awareness of SEC enforcement are more likely to issue first‐time going‐concern reports to distressed clients; where SEC “awareness” is measured using (i) audit office proximity to SEC regional offices, and (ii) proximity to specific SEC enforcement actions against auditors. We also show that these non‐Big 4 audit offices issue more going‐concern opinions to clients who do not subsequently fail, indicating a conservative bias that reduces the informativeness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…KAP size had a significant negative effect on ongoing concern audit opinion. The results of this study are consistent with the research of Krishnan (1994), Defond and Subramanyam (1998), and Defond et al (2018). Auditors believe that large companies can be more concerned than small companies.…”
Section: Yenny Watisupporting
confidence: 91%
See 2 more Smart Citations
“…KAP size had a significant negative effect on ongoing concern audit opinion. The results of this study are consistent with the research of Krishnan (1994), Defond and Subramanyam (1998), and Defond et al (2018). Auditors believe that large companies can be more concerned than small companies.…”
Section: Yenny Watisupporting
confidence: 91%
“…A company will choose high credibility KAP to improve the credibility of the financial statements on the external side as users of financial statements. Krishnan (1994), Defond and Subramanyam (1998), and Defond et al (2018) found a significant negative effect between KAP size and going concern audit opinion.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies examined: managers' decisions to temporarily exempt newly acquired business from Section 404 of Sarbanes-Oxley Act and found that managers are likely to use it when expected compliance costs are higher (Kravet et al 2018); the effect of expanded auditor's report in UK for large public companies on audit fees, audit quality and investors' reaction to release of auditors' reports and found no evidence (Gutierrez et al 2018); auditor monitoring of earn outs that arose as a consequence of SFAS 141 (R) in USA (Allee and Wangerin, 2018) prompting for high quality auditors; the different impact of legal systems characteristics and auditing standards (i.e. ISA) on audit behavior, improving it in USA, for instance, and affecting audit quality in China (Simunic et al 2017); how disclosures regarding internal controls weaknesses required by sections 302 and 404 of the Sarbanes-Oxley Act of 2002 (SOX) in USA, affect the market for corporate control, experiencing a substantially more negative market response and have lower future performance (Darrough et al 2018); the positive impact of the standard of prudence care (Maksymov and Nelson, 2017) in constraining negligence verdicts; conservative bias in the case of non-Big 4 audit offices in the proximity to SEC regional offices of to specific SEC enforcement actions against auditors (Defond et al 2018). The latter study make strong predictions about such conservative bias and compelling evidence that such non-Big 4 auditors are more likely to issue first-time going-concern reports to distressed clients.…”
Section: Discussionmentioning
confidence: 99%
“…The debate about the audit regulation and its ability to improve audit quality, which underpins a large segment of the literature, has resulted over the years in a positive association. On the other hand, there are studies documenting unexpected costs and reduces informativeness of audit reports (Defond et al 2018;Duellman et al 2018).…”
Section: Conclusion Limits and Scope For Future Researchmentioning
confidence: 99%